BASIC METHODS AND TECHNOLOGICAL SCHEMES FOR OBTAINING VEGETABLE OILS - Xakimov, Shavkat; Kamoliddinov, Muxammadali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In world practice, there are two main ways to obtain vegetable oils, which are fundamentally different from each other. These, mechanical compression of the oil, are called the pressing method, and melt the oil using a light volatile organic solvent, or extraction method. These binary methods can be used separately independently or together in a specific order. When used last year, this method is called forpressing-extraction. Regardless of which method is used, each method is carried out according to a specific technological scheme.Technological scheme is that of technological processes that are logically inextricably linked with each other, performed in the necessary order.